An assessment of the components of an effective monitoring and evaluation system in local NGOs : a case study of Earthchild project - Molapo, Lebogang Winfred (Stellenbosch : Stellenbosch University, 2019)
Thesis (MPA)--Stellenbosch University, 2019.